Effects of exercise of different intensities on withdrawal symptoms among people with substance use disorder: a systematic review and meta-analysis - Li, Hao; Su, Wantang; Cai, Jiajia; Zhao, Li; Li, Yan (Frontiers in Physiology, 2023)
Background: Exercise can effectively attenuate withdrawal symptoms and reduce relapse, but it is unknown whether exercise of different intensities produces different results. This study aimed to systematically review the effects of different exercise intensities on withdrawal symptoms among people with substance use disorder (SUD). Methods: Systematic searches for randomized controlled trials (RCTs) on exercise, SUD, and abstinence symptoms were conducted via electronic databases, including PubMed, up to June 2022. Study quality was evaluated using the Cochrane Risk of Bias tool (RoB 2.0) for assessment of risk of bias in randomized trials. The meta-analysis was performed by calculating the standard mean difference (SMD) in outcomes of interventions involving light-, moderate-, and high-intensity exercise for each individual study using Review Manager version 5.3 (RevMan 5.3). Results: In total, 22 RCTs (n = 1,537) were included. Overall, exercise interventions had significant effects on withdrawal symptoms, but the effect size varied with exercise intensity and by outcome measure (i.e., for different negative emotions). Light-, moderate-, and high-intensity exercise reduced cravings after the intervention [SMD = −0.71, 95% CI = (−0.90, −0.52)], and there were no statistical differences between the subgroups (p > 0.05). Light-, moderate-, and high-intensity exercise reduced depression after the intervention [light, SMD = −0.33, 95% CI = (−0.57, −0.09); moderate, SMD = −0.64, 95% CI = (−0.85, −0.42); high, SMD = −0.25, 95% CI = (−0.44, −0.05)], with moderate-intensity exercise producing the best effect (p < 0.05). Only light- and moderate-intensity exercise relieved anxiety after the intervention [light, SMD = −0.48, 95% CI = (−0.71, −0.26); moderate, SMD = −0.58, 95% CI = (−0.85, −0.31)]. Only high-intensity exercise worked in alleviating stress [SMD = −1.13, 95% CI = (−2.22, −0.04)]. Both irritability and restlessness could be improved by light- and moderate-intensity exercise [irritability, SMD = −0.74, 95% CI = (−0.98, −0.50); restless, SMD = −0.72, 95% CI = (−0.98, −0.47)], and there were no statistical differences between the subgroups (p > 0.05). Moderate- and high-intensity exercise decreased withdrawal syndrome after the intervention [moderate, SMD = −0.30, 95% CI = (−0.55, −0.05); high, SMD = −1.33, 95% CI = (−1.90, −0.76)], with high-intensity exercise producing the best effects (p < 0.01). Conclusion: Overall, exercise leads to improvements in withdrawal symptoms in individuals with SUD, but these effects vary significantly between the exercise of different intensities and according to the type of withdrawal symptoms. Moderate-intensity exercise has the greatest benefits in improving depression and anxiety; high-intensity exercise has the greatest benefits in improving withdrawal syndrome. Systematic Review Registration:www.crd.york.ac.uk/PROSPERO/, identifier, CRD42022343791